2015
DOI: 10.1109/tmi.2014.2337881
|View full text |Cite
|
Sign up to set email alerts
|

Energy Calibration of the Pixels of Spectral X-ray Detectors

Abstract: The energy information acquired using spectral X-ray detectors allows noninvasive identification and characterization of chemical components of a material. To achieve this, it is important that the energy response of the detector is calibrated. The established techniques for energy calibration are not practical for routine use in pre-clinical or clinical research environment. This is due to the requirements of using monochromatic radiation sources such as synchrotron, radio-isotopes, and prohibitively long tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…These events appear to be only one thus resulting in an information loss. It also leads to events in low energy ranges being detected which exceeds the maximum possible photon energy which also complicates the process of energy calibration and results in a loss of energy resolution [31]. Low X-ray flux was used with the brass filter protocol (protocol-1) to reduce the probability of the pileup effect whilst providing adequate statistics in a reasonable exposure time as shown in our previous studies [32,62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These events appear to be only one thus resulting in an information loss. It also leads to events in low energy ranges being detected which exceeds the maximum possible photon energy which also complicates the process of energy calibration and results in a loss of energy resolution [31]. Low X-ray flux was used with the brass filter protocol (protocol-1) to reduce the probability of the pileup effect whilst providing adequate statistics in a reasonable exposure time as shown in our previous studies [32,62].…”
Section: Discussionmentioning
confidence: 99%
“…Threshold equalization involves per-pixel calibration to reduce the intrinsic variations in the threshold levels associated with each counter and provides a consistent individual pixel response to a uniform X-ray flux [45]. The energy response of the detector was calibrated against the reference energies such as X-ray fluorescence (XRF) emitted from metallic foils (Mo and Pb) and γ-rays emitted from an Am-241 radioisotope [31]. …”
Section: Methodsmentioning
confidence: 99%
“…In this study the detector was operated in this chargesumming mode to minimize charge sharing effects. Energy calibration of the detector was performed with kVp technique [17] using a range of x-ray tube potentials.…”
Section: Spectral Scannermentioning
confidence: 99%
“…The energy calibration has been accomplished using monochromatic radiation sources of a known photon energy such as a synchrotron x-ray source [ 8 ], radio-isotopes [ 9 , 10 , 11 ], or x-ray fluorescent materials [ 12 , 13 , 14 ]. However, use of a monochromatic x-ray source for the energy calibration of every detector in mass production of x-ray imaging systems is not practical since most x-ray imaging systems are not easily configured to adopt monochromatic x-ray sources in them and it has a limitation of long measurement time [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a practical and efficient energy calibration method has been introduced in which the x-ray tube voltage is used as a reference for the energy calibration [ 15 , 16 ]. In this method, a global threshold of the comparators in the detector is found that makes 50% of the detector elements turned off at a given tube voltage, and then, the global threshold is supposed to be corresponding to the maximum photon energy determined by the peak tube voltage, that is, kVp.…”
Section: Introductionmentioning
confidence: 99%